2014
DOI: 10.1073/pnas.1413089111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional studies of Bud23–Trm112 reveal 18S rRNA N 7 -G1575 methylation occurs on late 40S precursor ribosomes

Abstract: The eukaryotic small ribosomal subunit carries only four ribosomal (r) RNA methylated bases, all close to important functional sites. N 7 -methylguanosine (m 7 G) introduced at position 1575 on 18S rRNA by Bud23-Trm112 is at a ridge forming a steric block between P-and E-site tRNAs. Here we report atomic resolution structures of Bud23-Trm112 in the apo and S-adenosyl-L-methionine (SAM)-bound forms. Bud23 and Trm112 interact through formation of a β-zipper involving main-chain atoms, burying an important hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
128
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 40 publications
(72 reference statements)
10
128
1
Order By: Relevance
“…9B). This suggests that Bud23 alone is not necessary for recruitment of Dhr1 to the preribosome, contrary to a recent report (21). Given that Utp14 also interacts with Dhr1, we asked if Utp14 is required for association of Dhr1 with the preribosome.…”
Section: Bscontrasting
confidence: 67%
See 3 more Smart Citations
“…9B). This suggests that Bud23 alone is not necessary for recruitment of Dhr1 to the preribosome, contrary to a recent report (21). Given that Utp14 also interacts with Dhr1, we asked if Utp14 is required for association of Dhr1 with the preribosome.…”
Section: Bscontrasting
confidence: 67%
“…We took advantage of the slowgrowth defect of bud23 mutants as a genetic entry point to dissect a constellation of functionally linked proteins. We found that mutations in DHR1, UTP2, or UTP14 partially suppressed the growth defect and 40S assembly defect of bud23⌬ mutants (18,21,23). We also showed that Bud23 binds to the N-terminal extension of Dhr1, making Bud23 a candidate for recruiting or regulating Dhr1 (24).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…It has now been well established both in yeast and human systems that, in some cases, enzymes bind to rRNA early in biogenesis, but do not actually catalyze a reaction until a later phase of maturation. 76,77 Similarly, in some cases enzymes modify RNAs in multiple classes, 78 so loss of function phenotypes must be analyzed with care. Thus it is crucial that, as researchers delve deeper into the functions of modifications in all RNA classes, the roles of the enzymes and the modifications themselves are disentangled.…”
Section: Rrnamentioning
confidence: 99%